Steel Structure Design for a 4-Story Apartment Building on Tanjungpura Street, Pontianak City - Repo, Marsianus; Leojarma, Anggara; Anggraini, Irene; Rasiwan (International Journal of Research in Vocational Studies (IJRVOCAS), 2026)
The construction of apartments on the banks of the Kapuas River in Pontianak City has become an urgent necessity due to high urbanization rates and limited land availability. The design of this steel structure uses the LRFD method based on SNI 1729:2020, SNI 7860:2020, SNI 1726:2019, and SNI 2847-2019 with a Regular Moment Resisting Frame System. The four-story building, measuring 40x30 meters and made of BJ37 steel, uses composite floor slabs, with steel profiles consisting of main beams. The design uses a Moment Resisting Frame (MRF) system to withstand lateral loads on soft soil in Pontianak. The analysis results show a maximum inter-story drift of 26.7 mm, still far below the 80 mm limit according to SNI 1726:2019. This study confirms that the use of BJ37 steel with composite plates significantly reduces dead loads compared to conventional concrete, making it a viable solution for the area. Structural connections at the intersections of beams and columns use high-quality A325 bolts.